Advanced protection against environmental degradation of silver mirror stacks for space application. (20th February 2021) - Kurapati, Rajendra; Maurice, Vincent; Seyeux, Antoine; Klein, Lorena H.; Mercier, Dimitri; Chauveau, Grégory; Grèzes-Besset, Catherine; Berthod, Loïc; Marcus, Philippe
Abstract: Protection of silver mirror stacks from environmental degradation before launching is crucial for space applications. Hereby, we report a comparative study of the advanced protection of silver mirror stacks for space telescopes provided by SiO2 and Al2 O3 coatings in conditions of accelerated aging by sulfidation. The model silver stack samples were deposited by cathodic magnetron sputtering on a reference silica substrate for optical applications and a surface-pretreated SiC substrate. Accelerated aging was performed in dry and more severe wet conditions. Optical micrographic observations, surface and interface analysis by Time-of Flight Secondary Ion Mass Spectrometry (ToF-SIMS) and reflectivity measurements were combined to comparatively study the effects of degradation. The results show a lower kinetics of degradation by accelerated aging of the stacks protected by the alumina coating in comparable test conditions.